Regulation of Stress Granule Formation by Inflammation, Vascular Injury, and Atherosclerosis - Herman, Allison B; Silva Afonso, Milessa; Kelemen, Sheri E; Ray, Mitali; Vrakas, Christine N; Burke, Amy C; Scalia, Rosario G; Moore, Kathryn; Autieri, Michael V (Arteriosclerosis, thrombosis, and vascular biology, 2019)
Stress granules (SGs) are dynamic cytoplasmic aggregates containing mRNA, RNA-binding proteins, and translation factors that form in response to cellular stress. SGs have been shown to contribute to the pathogenesis of several human diseases, but their role in vascular diseases is unknown. This study shows that SGs accumulate in vascular smooth muscle cells (VSMCs) and macrophages during atherosclerosis. Approach and Results: Immunohistochemical analysis of atherosclerotic plaques from LDLR mice revealed an increase in the stress granule-specific markers Ras-G3BP1 (GTPase-activating protein SH3 domain-binding protein) and PABP (poly-A-binding protein) in intimal macrophages and smooth muscle cells that correlated with disease progression. In vitro, PABP+ and G3BP1+ SGs were rapidly induced in VSMC and bone marrow-derived macrophages in response to atherosclerotic stimuli, including oxidized low-density lipoprotein and mediators of mitochondrial or oxidative stress. We observed an increase in eIF2α (eukaryotic translation initiation factor 2-alpha) phosphorylation, a requisite for stress granule formation, in cells exposed to these stimuli. Interestingly, SG formation, PABP expression, and eIF2α phosphorylation in VSMCs is reversed by treatment with the anti-inflammatory cytokine interleukin-19. Microtubule inhibitors reduced stress granule accumulation in VSMC, suggesting cytoskeletal regulation of stress granule formation. SG formation in VSMCs was also observed in other vascular disease pathologies, including vascular restenosis. Reduction of SG component G3BP1 by siRNA significantly altered expression profiles of inflammatory, apoptotic, and proliferative genes. These results indicate that SG formation is a common feature of the vascular response to injury and disease, and that modification of inflammation reduces stress granule formation in VSMC.